Evaluation of the Effect of Virtual Reality Glasses Used on Cancer Patients Receiving Outpatient Chemotherapy on Adaptation and Adherence To Treatment - Öz, Gözde (My University, 2024)
Araştırma, ayaktan kemoterapi alan kanser hastalarında kullanılan sanal gerçeklik gözlüğünün anksiyete ve tedaviye uyuma etkisinin değerlendirilmesi amacıyla randomize kontrollü olarak gerçekleştirildi. Bir araştırma hastanesinde ayaktan kemoterapi ünitesinde 1 Nisan- 31 Eylül 2023 tarihleri arasında 21 günde bir intravenöz kemoterapi tedavisi alan 15 deney, 15 kontrol grubu olmak üzere toplam 30 hasta çalışmanın örneklemini oluşturdu. Araştırma verileri Hasta Bilgi Formu, Beck Anksiyete Ölçeği (BAÖ), Kronik Hastalıklara Uyum Ölçeği (KHUÖ) ve Sanal Gerçeklik Gözlüğü kullanılarak toplandı. Verilerin değerlendirilmesinde bağımsız gruplarda kategorik değişkenlerin oranları arasındaki farklar Ki-Kare testleri ile analiz edildi. İki bağımsız grup arasında niceliksel sürekli verilerin karşılaştırılmasında t-testi kullanıldı. Grup içi ölçümlerin karşılaştırılmasında bağımlı gruplar t-testi kullanıldı. Araştırma hakkında bilgi verdikten sonra her iki gruptaki hastalara ön-test uygulandı. Deney grubundaki hastalara 3 kür kemoterapi tedavisi boyunca sanal gerçeklik gözlüğü ile 3 farklı video izletildi, 3. kür sonunda iki gruba da son test uygulandı. Hastaların gruba göre anksiyete son-test ölçümleri anlamlı farklılık gösterdi (t(28)=3.132; p=0.004<0,05). Kontrol grubunda anksiyete son-test ölçümleri (x̄=12,067), deney grubunda anksiyete son-test ölçümlerinden (x̄=6,667) yüksek bulundu. Hastaların gruba göre kronik hastalıklara uyum toplam son-test ölçümleri anlamlı farklılık gösterdi (t(28)=-3.687; p=0.001<0,05). Deney grubunda kronik hastalıklara uyum toplam son-test ölçümleri (x̄=98,400), kontrol grubunda kronik hastalıklara uyum toplam son-test ölçümlerinden (x̄=87,067) yüksek bulundu. Ayaktan kemoterapi alan kanser hastalarında kullanılan sanal gerçeklik gözlüğünün anksiyeteyi azaltıp tedaviye uyumu arttığı saptandı. Anahtar Kelimeler: Anksiyete, kemoterapi, sanal gerçeklik, tedaviye uyum

The study was conducted in a randomized controlled manner to evaluate the effects of virtual reality glasses used on anxiety and treatment compliance in cancer patients receiving outpatient chemotherapy. A total of 30 patients, including 15 experimental and 15 control groups, who received intravenous chemotherapy treatment every 21 days between April 1 and September 31, 2023, in an outpatient chemotherapy unit at a research hospital, constituted the sample of the study. Research data were collected using the Patient Information Form, Beck Anxiety Scale (BAI), and Chronic Disease Adaptation Scale (CHIS). In evaluating the data, differences between the rates of categorical variables in independent groups were analyzed with Chi-Square tests. The t-test was used to compare quantitative continuous data between two independent groups. Dependent groups t-test was used to compare measurements within groups. After giving information about the research, a pre-test was administered to patients in both groups. Patients in the experimental group were shown 3 different videos with virtual reality glasses during 3 cycles of chemotherapy treatment, and a posttest was administered to both groups at the end of the 3rd cycle. Anxiety post-test measurements of the patients showed a significant difference according to the group (t(28)=3.132; p=0.004<0.05). Anxiety post-test measurements in the control group (x̄=12.067) were found to be higher than anxiety post-test measurements in the experimental group (x̄=6.667). Total post-test measurements of patients' adaptation to chronic diseases showed a significant difference according to group (t(28)=-3.687; p=0.001<0.05). Total post-test measurements of adaptation to chronic diseases in the experimental group (x̄=98.400) were found to be higher than total post-test measurements of adaptation to chronic diseases in the control group (x̄=87.067). It was found that virtual reality glasses used in cancer patients receiving outpatient chemotherapy reduced anxiety and increased compliance with treatment. Keywords: Anxiety, chemotherapy, treatment compliance, virtual reality
Ayaktan Kemoterapi Alan Kanser Hastalarında Kullanılan Sanal Gerçeklik Gözlüğünün Anksiyete ve Tedaviye Uyuma Etkisinin Değerlendirilmesi
Keywords: Hemşirelik; Onkolojik hemşirelik; Nursing; Oncologic nursing